Lung dendritic cells induce migration of protective T cells to the gastrointestinal tract. - LAVELLE, EDWARD (My University, 2013)
Developing efficacious vaccines against enteric diseases is a global challenge that requires a better understanding of cellular recruitment dynamics at the mucosal surfaces. The current paradigm of T cell homing to the gastrointestinal (GI) tract involves the induction of α4β7 and CCR9 by Peyer's patch and mesenteric lymph node (MLN) dendritic cells (DCs) in a retinoic acid-dependent manner. This paradigm, however, cannot be reconciled with reports of GI T cell responses after intranasal (i.n.) delivery of antigens that do not directly target the GI lymphoid tissue. To explore alternative pathways of cellular migration, we have investigated the ability of DCs from mucosal and nonmucosal tissues to recruit lymphocytes to the GI tract. Unexpectedly, we found that lung DCs, like CD103(+) MLN DCs, up-regulate the gut-homing integrin α4β7 in vitro and in vivo, and induce T cell migration to the GI tract in vivo. Consistent with a role for this pathway in generating mucosal immune responses, lung DC targeting by i.n. immunization induced protective immunity against enteric challenge with a highly pathogenic strain of Salmonella. The present report demonstrates novel functional evidence of mucosal cross talk mediated by DCs, which has the potential to inform the design of novel vaccines against mucosal pathogens.
PUBLISHED
PMID: 23960190
Keywords: enteric diseases; Immunology, Inflammation & Infection